American GI Forum 1991 - San Jose Queen Rehearsal (and Other Event) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1991 American GI Forum - San Jose chapter Queen Coronation rehearsal. Includes videos from February 26 (36:14) and March 5 (42:02). Also included is a review of the 1996 GI Forum Queen Coronation (45:49).